Dampak Pendampingan Corporate Social Responsibility (CSR) PT Astra Internasional pada Pembangunan Desa Wisata Kota Tua Jamblang Kabupaten Cirebon: (Social Return on Investment (SROI) analysis) - Ana Melani; Tommi Hidayat; Nurul Chamidah (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
Jamblang Village is a village located in Cirebon Regency. Jamblang Village in 2022 is included in the 300 villages that will receive the Indonesian Tourism Village Award (ADWI 2022) from the Ministry of Tourism and Creative Economy or the Tourism and Creative Economy Agency (Kemenparekraf or Ayahrekraf). Jamblang Village has only received an empowerment assistance program towards tourism villages in the last two years but has been able to show the development of the fostered results, namely an increasingly diverse network of cooperation to strengthen the tourism village work program, obtain funding within three years of mentoring, as well as the increasing number of people joining the program. active pokdarwis members. The research method is qualitative. Collecting data through interviews, discussion forums, and observations. The results of the study found that the impact of mentoring and empowerment in Jamblang Village through SROI analysis was that there were three impacts. Social impact, environmental impact, economic impact. The social impact in the form of enthusiasm and commitment of the community who are members of the tourism awareness group increases in realizing the agreed work program. The environmental impact is by decorating the tourist environment with historical insight into Jamblang Village. The economic impact of tourism-aware groups getting free photography training and khas pecinan cakes is starting to be in demand again.